Punica Granatum Peel Extract Protects Against Ionizing Radiation-Induced Enteritis And Leukocyte Apoptosis In Rats - YEGEN, BERRAK; GÜÇLÜ, HÜLYA (OXFORD UNIV PRESS, 2009)
Apoptosis/Cytokine/Enteritis/Ileum/Irradiation/Punica granatum/Pomegranate/Radioprotective. Radiation-induced enteritis is a well-recognized sequel of therapeutic irradiation. Therefore we examined the radioprotective properties of Punica granatum peel extract (PPE) on the oxidative damage in the ileum. Rats were exposed to a single whole-body X-ray irradiation of 800 cGy. Irradiated rats were pretreated orally with saline or PPE (50 mg/kg/day) for 10 days before irradiation and the following 10 days, while control rats received saline or PPE but no irradiation. Then plasma and ileum samples were obtained. Irradiation caused a decrease in glutathione and total antioxidant capacity, which was accompanied by increases in malondialdehyde levels, myeloperoxidase activity, collagen content of the tissue with a concomitant increase 8-hydroxy-2'-deoxyguanosine (an index of oxidative DNA damage). Similarly, pro-inflammatory cytokines (TNF-alpha, IL-1 beta and IL-6) and lactate dehydrogenase were elevated in irradiated groups as compared to control. PPE treatment reversed all these biochemical indices, as well as histopathological alterations induced by irradiation. Furthermore, flow cytometric measurements revealed that leukocyte apoptosis and cell death were increased in irradiated animals, while PPE reversed these effects. PPE supplementation reduced oxidative damage in the ileal tissues, probably by a mechanism that is associated with the decreased production of reactive oxygen metabolites and enhancement of antioxidant mechanisms. Adjuvant therapy of PPE may have a potential to support a Successful radiotherapy by protecting against radiation-induced enteritis.
Keywords: PROSTATE-CANCER; OXIDATIVE STRESS; POMEGRANATE; ANTIOXIDANTS; INFLAMMATION; IRRADIATION; L.; CHEMOPREVENTION; DYSFUNCTION; INJURY